Engine downsizing simulation based on low rpm variable valve timing system - Sabaruddin, Ainul Aniyah (2015)
Downsizing an engine has proven to be one of an effective way to reduce emissions and fuel consumption. Theoretically, when an engine is running at high speed, maximum overlapping between the intake and exhaust valve is needed for a lean „breathing‟ of the engine. But when an engine is running at lighter speed and load, these maximum overlapping techniques may be useful to be use to lessen the engine‟s fuel consumptions and emissions. To optimize these „breathing‟ of the engine, it requires a different set of valve timing at different speed. This is due to the fact that as the speed increases, the duration of intake valve to have more fresh air decreases and combusted gas may not exit the chamber in time. Therefore, varying the intake timing of an engine could help produce higher power and, if applied to smaller and lighter engine, it could result in a lower fuel consumption as well. In this particular research that has been conducted through simulations and complemented by experimental works, it has been realized that downsizing an engine together with the implementation of variable valve timing is able to generate similar power with an increase in volumetric efficiency, while slightly lowering fuel consumption. As reported by many researchers, the variable valve timing method is indeed proven for improved fuel economy, lower emissions and higher torque under any operating condition